Can energy sector reach carbon neutrality with biomass limitations?. (15th June 2022) - Ozoliņa, Signe Allena; Pakere, Ieva; Jaunzems, Dzintars; Blumberga, Andra; Grāvelsiņš, Armands; Dubrovskis, Dagnis; Daģis, Salvis
Abstract: The energy transformation sector, including district heating (DH), is vital in reaching long-term emission reductions and thus climate neutrality set by the European Commission. Biomass for energy production continues to grow in countries with extensive forest resources, e.g. Latvia. However, growing global demand obligates increasing the added value of bioresources, reducing their availability for the energy sector as it is a low value-added application. Therefore, an effective and competitive DH system cannot be developed without high energy efficiency increase of the existing heating infrastructure and building stock. In this study TIMES model supplemented with results of the System Dynamics model and biomass forecasting model was used to elaborate an analysis of the energy transformation sector development. The impact of measures defined in the National Energy and Climate Plan until 2030 and the energy sector pathways towards climate neutrality until 2050 in Latvia was analysed by setting biomass limitations for the energy sector use. Results show that it would be possible to decarbonise the energy sector. Still, it is necessary to increase energy efficiency in the building stock and heating infrastructure and promote renewable sources in the energy transformation sector, including heat pumps and solar energy. It would require an additional investment of more than 326 million EUR compared to the Base scenario. Highlights: Linear optimisation model Times is used for energy sector modelling. The potential energy efficiency savings are derived from soft-linked system dynamics model. The biomass availability is determined through forest resource optimisation model. Results show that it would be possible to decarbonise the district heating and power sectors. Decarbonisation would require an additional investment of more than 326 MEUR.